Leaching Zn, Cd, Pb, and Cu from Wastewater Sludge Using Fenton Process - Abooalfazl Azhdarpoor; Rabieh Hoseini; Mansoureh Dehghani (Journal of Health Sciences and Surveillance System, 2015)
Background: High amount of heavy metals in sludge is one of the major obstacles to its use on farms. The present study aimed to investigate the possibility of leaching heavy metals from wastewater sludge by Fenton method and determine the optimum level of parameters, such as iron, hydrogen peroxide, time, and pH for Fenton reaction. Methods: The effects of various parameters, such as pH (2-9), hydrogen peroxide concentration (0.5-6 g/l), Fe concentration (0.5-4 g/l), and leaching time (5-60 min), were studied. Results: The results showed that the optimal condition for leaching of heavy metals occurred at pH of 2-3, hydrogen peroxide concentration of 3 g/l, iron concentration of 2 g/l, and leaching time of 15 min. Under these optimal conditions, 92% of Zn, 100% of Cd, 100% of Pb, and 80% of Cu were leached from the wastewater sludge. Conclusions: Fenton method can leach heavy metals from wastewater sludge through decomposition of organic materials at H2O2/Fe ratio of 1.5:2.